The Urban Library. Creative City Branding in Spaces for All. - Nevárez, Julia (Springer, 2021)
This book examines the role, history and function of public libraries in contemporary societies as motors that drive development. It analyses through case studies, how contemporary libraries have been redesigned to offer a new kind of public space while also reshaping neglected areas in cities. Broadly understood the book seeks to comprehend contemporary library design, urban development and the revitalization of specific urban areas. Important and world famous architects – star-architects – have designed signature architecture in the contemporary libraries selected for this volume. The examples to be showcased in the book include the main Seattle Public Library, Salt Lake City Public Library, New York Public Library, Spain Library Medellin, Colombia, Halifax Central Library Nova Scotia, Canada and Library of Alexandria in Egypt to offer examples of what constitute the approach to libraries and urban development in many cities around the world nowadays. Data in the form of interviews to library directors, librarians and users, tours of libraries, visual documentation and archival research have been collected for most public libraries included as case studies for the book.
Keywords: Bibliotheksbau; Öffentliche Bibliothek; Stadtentwicklung; Öffentlicher Raum; Stadtbild; Architektur; Nutzungsflexibilität